Information Exposure and Fashion Accessories Buying Decision Behavior - Sitdhikornkrai, Kittilada; Intaratat, Kamolrat; Lomchawakarn, Piyachat (Interdisciplinary Academic and Research Journal, 2023)
The Covid-19 crisis affects every life and every business on the planet, causing raw materials in the production chain to be affected. Sales of jewelry products are affected by slow economic growth, high cost of living, and consumers slow down purchases or buy only what is needed. However, various digital media play a role in changing the behavior of consumers’ perception of news or information search. Thus, this study is intended to investigate 1) information exposure behavior relating to fashion accessories; 2) fashion accessory buying decision behavior; and 3) the relationship between information exposure behavior and fashion accessory buying decision behavior. This research was quantitative, using a survey methodology. A multi-stage sampling method was used to collect data from 400 fashion accessory buyers in Bangkok. Initially, a simple random sampling using the lottery method was used to select 8 different districts in Bangkok. The second stage was to choose only people who previously bought fashion accessories from fashion accessory stores. Questionnaires were utilized as instruments. The following descriptive and inferential statistics were used to examine the data: Frequency, Percentage, Arithmetic Mean, Standard Deviation, one-way ANOVA, Significant Difference Analysis, and Correlation Analysis using the Pearson Product – Moment Correlation Coefficients. The study’s findings indicated that 1) the sample group’s information exposure behavior was mostly via Facebook. The frequency of information exposure was observed to be almost every day, with the highest exposure time being between 6:00 p.m. and 9:00 p.m. The average time spent receiving information is 1 hour. The following factors influence information exposure, respectively: creative images and video clips. 2) The sample group prefers earrings. Secondly, the ready-to-deliver products and simple black-and-white. Moreover, since they could check prices first, the majority of the sample groups purchased products via online channels. The majority of the sample group purchased an average of 2-3 pieces at a time, at a cost of roughly 900 baht per piece, virtually every week by paying via mobile banking online; and 3) The relationship between information exposure behavior and fashion accessories buying decision behavior demonstrated a significant positive correlation at the 0.002 level between information exposure and fashion accessories buying decision behavior. Furthermore, the average duration per time of information exposure and buying behavior revealed a significant positive correlation at the 0.001 level.